Kurangnya kesadaran dan motivasi pelanggan: Pembayaran pajak dan bangunan - Alisa, Siti Nur (Maliki Interdisciplinary Journal, 2024)
This investigate points to form a bank mindful of paying charges with the level of mindfulness and level of inspiration in paying charges and buildings in Lemang town, West Rangsang sub-district, Pulau Meranti Regency. This examination strategy is within the shape of information examination which employments quantitative examination with approval tests and unwavering quality tests, numerous examination, classical presumption tests. The comes about of this investigate somewhat appear that this need of mindfulness and inspiration will have an affect on the victory of a country and state in advancement for the welfare of society, so there’s a need for reserves for improvement costs to realize objectives, one way to attain these objectives is by paying charges. The level of mindfulness features a noteworthy impact on people’s inspiration to pay arrive and building charges. Too, the level of mindfulness and level of benefit have a critical impact on people’s inspiration to pay arrive and building charges with the remaining 71.3% impacted by other factors not clarified in this inquire about.